Case report: Ventricular primary central nervous system lymphoma with partial hypointensity on diffusion-weighted imaging - Li, Xintong; Xiong, Hua (Frontiers in Neurology, 2022)
Introduction: Primary central nervous system lymphoma (PCNSL) is infrequent and represents 3.1% of primary brain tumors. It’s extremely rare which are confined to the ventricular system, especially the third ventricle. There are few literatures or case reports to date. We report a case of PCNSL with partial hypointensity on diffusion weighted imaging (DWI) located in the lateral and third ventricle. Then we discuss other ventricular tumors with similar imaging findings. Case presentation: A 78-year-old man presented with memory deterioration and slow response without obvious precipitating factor for one week. Magnetic resonance imaging (MRI) showed lesions in the third ventricle and left lateral ventricle, which were slightly hypointense on T1-weighted imaging (T1WI), isointense to slightly hypointense on T2-weighted imaging (T2WI). On DWI, the left lateral ventricular lesion was hyperintense, while th third ventricular lesion was hypointense. After surgical procedure, the pathology and immunohistochemistry revealed diffuse large B-cell lymphoma (DLBCL). Conclusions: Ventricular PCNSL is quite rare, and may be confused with other tumors in the same position. However, PCNSL differs from other central nervous system tumors in that it is primarily treated with chemotherapy and/or radiation therapy. So, it is important to recognize PCNSL and differentiate it from other tumors, considering its implications on management planning.